Numerical and experimental investigations on the heat transfer enhancement in corrugated channels using SiO2-water nanofluid - Ahmed M.A.; Yusoff M.Z.; Ng K.C.; Shuaib N.H. (Elsevier Ltd, 2023)
Channel flow; Finite volume method; Heat convection; Heat transfer; Heat transfer coefficients; Iterative methods; Numerical methods; Reynolds number; Silica; Turbulent flow; Volume fraction; Collocated finite volume methods; Convective heat transfer; Corrugated channel; Experimental investigations; Heat Transfer enhancement; Low Reynolds number; Nanofluids; Thermal characteristics; Nonisothermal flows; Nanofluidics